2017
DOI: 10.1016/j.plaphy.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A harpin elicitor induces the expression of a coiled-coil nucleotide binding leucine rich repeat (CC-NB-LRR) defense signaling gene and others functioning during defense to parasitic nematodes

Abstract: The bacterial effector harpin induces the transcription of the Arabidopsis thaliana NON-RACE SPECIFIC DISEASE RESISTANCE 1/HARPIN INDUCED1 (NDR1/HIN1) coiled-coil nucleotide binding leucine rich repeat (CC-NB-LRR) defense signaling gene. In Glycine max, Gm-NDR1-1 transcripts have been detected within root cells undergoing a natural resistant reaction to parasitism by the syncytium-forming nematode Heterodera glycines, functioning in the defense response. Expressing Gm-NDR1-1 in Gossypium hirsutum leads to resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 164 publications
5
44
0
Order By: Relevance
“…Experiments presented here show that G. max MAPKs (MAPKs) identified to be expressed within parasitized root cells undergoing the process of defense to the root pathogenic nematode Heterodera glycines often presage their function in defense. Experiments show the relationship between PTI and ETI and the defense MAPKs to prior published work (Matsye et al 2011Pant et al 2014Pant et al , 2015Sharma et al 2016;McNeece et al 2017;Aljaafri et al 2017;. As presented in earlier experiments, PTI has been studied here by examining ENHANCED DISEASE SUSCEPTIBILITY1 (EDS1) and LESION SIMULATING DISEASE1 (LSD1) (Dietrich et al 1997;Aarts et al 1998;Falk et al 1999;Pant et al 2014Pant et al , 2015Matuszkiewicz et al 2018).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Experiments presented here show that G. max MAPKs (MAPKs) identified to be expressed within parasitized root cells undergoing the process of defense to the root pathogenic nematode Heterodera glycines often presage their function in defense. Experiments show the relationship between PTI and ETI and the defense MAPKs to prior published work (Matsye et al 2011Pant et al 2014Pant et al , 2015Sharma et al 2016;McNeece et al 2017;Aljaafri et al 2017;. As presented in earlier experiments, PTI has been studied here by examining ENHANCED DISEASE SUSCEPTIBILITY1 (EDS1) and LESION SIMULATING DISEASE1 (LSD1) (Dietrich et al 1997;Aarts et al 1998;Falk et al 1999;Pant et al 2014Pant et al , 2015Matuszkiewicz et al 2018).…”
Section: Introductionmentioning
confidence: 61%
“…Among the 229 induced genes were the G. hirsutum NDR1 (Gh-NDR1) and MPK7 (CM081B01) (Miao et al 2010). Consequently, the involvement of harpin during G. max defense to different parasitic nematodes, including H. glycines, Meloidogyne incognita and Rotylenchulus reniformis, is consistent with its important role in defense signaling (Gopalan et al 1996;Aljaafri et al 2017).…”
Section: Harpin and Ndr1 Relate To Mapk Signaling And Defense Responsmentioning
confidence: 91%
See 2 more Smart Citations
“…Aljaafri et al. () found that a harpin elicitor can function to turn on plant defences in H. glycines in soybean, and M. incognita and R. reniformis in cotton in susceptible cultivars.…”
Section: Introductionmentioning
confidence: 99%